Risk capital’s attitude to financing innovation - Pohulak-Żołędowska, Elżbieta (Kapitał ryzyka w finansowaniu innowacji, 2018)
In hereby article the author discusses the problem of financing innovation, especially the disruptive (or breakthrough) innovation. High uncertainty, capital intensity, but also high profit perspective make investing in innovations potentially attractive. There is a common perception that venture capital has become an intermediary in financial markets, providing capital to firms that might otherwise have difficulty attracting financing. As these firms are thought to be small, young and innovative, plagued by the “liability of newness”, venture capital is expected to fulfill an important role in the economy ‒ it is meant to be a tool of financing to novel and risky ventures and, hence, it is a drive of the technological and economic progress. The goal of the article is an attempt to answer the question if the venture capital is a risk loving or risk averse capital. Methods used are: critical analysis of literature and data analysis
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 529; s. 237-247
Keywords: innovation; risk; uncertainty; venture capital; innowacje; ryzyko; niepewność; kapitał venture